Obtenção de membrana náilon/fibroína eletrofiada utilizada na adsorção de corantes industriais - Bortolotto, Viviane Benetti (2024)
Silk fibroin is a natural biopolymer originating from Bombyx mori, which presents remarkable thermal stability and high mechanical resistance. During industrial processes, a portion of this biopolymer is discarded due to the occurrence of defects in parts of the cocoons. A promising solution for using this waste is to incorporate it into blend systems, allowing the creation of materials destined for the textile industry. Polymeric membranes have emerged as effective tools for water purification since the 1960s, demonstrating high efficiency in contaminant removal. This study employed electrospinning technique to manufacture PA66/fibroin nanofiber membranes with compositions of (w:w) 100:0 (NP), 87.5:12.5 (NF125), 75:25 (NF250) and 50:50 (NF500). The materials produced were characterized using Fourier transform infrared absorption spectroscopy techniques – attenuated total reflection (FTIR-ATR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), tests Traction analysis, X-ray diffraction (XRD) and ultraviolet visible spectroscopy (UV-Vis) were performed to characterize the polymeric systems and evaluate the filtration efficiency using rhodamine B solution. These analyzes identified interactions between fibroin and PA66, impacting the membrane crystallinity, morphology, elasticity and thermal stability. In filtration experiments, the electrospun membranes outperformed the commercial membrane in removing Rhodamine B dye. NF125 and NF250 exhibited superior physicochemical properties, Therefore, these results point to the potential use of PA66/fibroin membranes in textile industry contaminant treatment applications, offering an efficient and sustainable solution for Rhodamine B removal.